Rule of Law and Financial Performance of Oil Companies of Pakistan - Ayesha Seerat; Dr. Sumaira Ghaffar; Dr. Syed Arif Hussain Shah; Dr. Attaullah; Syed Hilal Mubarik (Social Science Review Archives, 2025)
This study investigates the impact of the rule of law on the financial performance of oil companies in Pakistan, offering novel insight into how institutional quality influences firm-level outcomes within a key strategic sector. Grounded in institutional theory, which posits that organizations are shaped by the formal and informal structures in their external environment, the research highlights how the strength or weakness of legal institutions directly affects corporate behavior, governance, and financial returns. Using panel data methodology, the study draws on secondary data from the annual reports of listed oil companies in Pakistan, complemented by macro-level data on oil prices and rule of law indices sourced from the World Bank. Empirical results reveal a statistically significant positive relationship between the rule of law and Return on Assets (ROA), underscoring that stronger institutional environments facilitate better financial outcomes. This aligns with institutional theory, which suggests that robust legal frameworks reduce transaction costs, enhance investor confidence, and promote efficient allocation of resources—factors critical to firm profitability. Conversely, weak rule of law environments introduce uncertainty, increase compliance risks, and undermine long-term strategic planning. This research contributes to the growing body of literature on governance and financial performance by isolating the rule of law as a core institutional determinant within the Pakistani context. It also underscores the need for policy reform aimed at strengthening legal institutions, promoting accountability, and ensuring transparency in the oil sector. The study acknowledges its limitation in focusing exclusively on the rule of law as a single dimension of corporate governance.